The Victorian gothic : an Edinburgh companion - Smith, Andrew, 1964-; Hughes, William, 1964- (Edinburgh University Press, 2012)
These 14 chapters, each written by an acknowledged expert in the field, provide an invaluable insight into the complex and various Gothic forms of the nineteenth century. Covering a range of diverse contexts, the chapters focus on science, medicine, Queer theory, imperialism, nationalism, and gender. Together with further chapters on the ghost story, realism, the fin de siÃ·cle, pulp fictions, sensation fiction, and the Victorian way of death, the Companion provides the most complete overview of the Victorian Gothic to date. The book is an essential resource for students and scholars working on the Gothic, Victorian literature and culture, and critical theory.